Impact of market orientation on competitiveness: Analysis of internationalized medium-sized and large enterprises - Miklós Stocker; Lídia Várkonyi (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The objective of this article is to identify the impact of market orientation on company competitiveness of internationalized medium and large enterprises present in Central Eastern Europe and/or Western Europe in the period of economic growth. Research Design & Methods: Quantitative large sample statistical analysis was conducted on a sample of Hungarian internationalized medium and large sized enterprises (n=119). Data was obtained by the survey method, MKTOR scale was implemented in the survey and financial data was also included. The sample is representative for size and the sample size is larger than required. Factor analysis was used to determine the components of market orientation, regression analysis was used to test the hypotheses and Chi-square test were used to determine differences in the elements of customer orientation. Findings: Market orientation influences the competitiveness of internationalized medium and large sized enterprises present in Central Eastern Europe and/or Western Europe. Among the components of market orientation, competitor orientation had the most significant and most powerful impact on competitiveness and on market performance as well. Interfunctional coordination had significant impact on adaptivity and operationality. Customer orientation, however, did not have significant impact on either competitiveness or its elements, because customer orientation became a threshold capability of internationalized medium and large sized enterprises which are present in Central Eastern Europe and/or in Western Europe. Implications & Recommendations: Executive managers of internationalized medium and large enterprises should focus on competitor orientation if they would like to increase their competitiveness and market performance, while they should maintain their companies' high level of customer orientation. If managers would like to increase their companies' adaptivity and/or operationality then they should also focus on interfunctional coordination procedures as well. Contribution & Value Added: The article is about medium and large sized internationalized enterprises which is an underresearched area and the sample's representativity is also unique. The main contribution of the article is that customer orientation is a threshold capability of internationalized medium and large sized enterprises, and we also prove that market orientation and especially competitor orientation increases the competitiveness of internationalized medium and large sized companies.
Keywords: M16; F23; L10; 330; Company Competitiveness; Market Orientation; Competitor Orientation; Medium and large sized enterprises; MKTOR scale